The Too-Important-to-Fail Conundrum : Impossible to Ignore and Difficult to Resolve - Otker, Inci (Staff Discussion Notes; Staff Discussion Notes ;, 2011)
DISCLAIMER: This Staff Discussion Note represents the views of the authors and does not necessarily represent IMF views or IMF policy. The views expressed herein should be attributed to the authors and not to the IMF, its Executive Board, or its management. Staff Discussion Notes are published to elicit comments and to further debate.